Filling vacancies in a Prussian blue analogue using mechanochemical post-synthetic modification. Issue 57 (12th June 2020) - Cattermull, John; Wheeler, Samuel; Hurlbutt, Kevin; Pasta, Mauro; Goodwin, Andrew L.
Abstract : Mechanochemical grinding offers a method of reducing the vacancy concentration of Prussian blue analogues. Abstract : Mechanochemical grinding of polycrystalline powders of the Prussian blue analogue (PBA) Mn[Co(CN)6 ]2/3 □1/3 · x H2 O and K3 Co(CN)6 consumes the latter and chemically modifies the former. A combination of inductively-coupled plasma and X-ray powder diffraction measurements suggests the hexacyanometallate vacancy fraction in this modified PBA is reduced by approximately one third under the specific conditions we explore. We infer the mechanochemically-driven incorporation of [Co(CN)6 ] 3− ions onto the initially-vacant sites, coupled with intercalation of charge-balancing K + ions within the PBA framework cavities. Our results offer a new methodology for the synthesis of low-vacancy PBAs.